Pengaruh Media PALINGBADA Terhadap Pemahaman Konsep Keliling Bangun Datar Di Kelas III Sekolah Dasar - Virra Septiani Suherman Virra; Isrok’atun; Ani Nur Aeni (Elementary Teacher Education Program, Majalengka University, 2023)
This study was interrupted with the problem of students having difficulty in understanding the concept of flat buildings, because in the teaching learning process, teachers only explain directly from examples of issues and how to solve them without guiding or directing students to understand the concept in advance, without the presence of relevant media to discern the concept. The purpose of the research was to find out the influence of PALINGBADA media on the understanding of the concept of two-dimensional circumference in Grade III of Elementary School and to know that there are differences in the influences of PALINGBADA and conventional media on understanding the concepts of two-dimensional circumference at Grade III of Elementary School. The research uses experimental methodologies, the type of research used is quasi-experimental with a design of non-equivalent groups. In particular, the research instrument is a test consisting of multiple-choice questions. Data analysis that are used, including independent sample t-tests, n-gain tests, homogeneity testing, and normality procedures. The results of the research showed that there was a media influence of PALINGBADA on the understanding of the concept of two-dimensional in class III and there was an influence difference between the media and conventional media on understanding of two-dimensional concepts in the class III of the Elementary School.